Modeling water quality index to assess shallow groundwater quality for sustainable utilization in Southern India - Anbazhagan, Siddan; Jothibasu, Arumugam (International Journal of Advanced Geosciences, 2014)
In sustainable groundwater study, it is necessary to assess the quality of groundwater in terms of drinking and irrigation purposes. The present study attempt to assess the groundwater quality through Drinking Water Quality Index (DWQI) and Irrigation Water Quality Index (IWQI) in hard rock aquifer system and sustainable water use in Uppar Odai sub-basin, Southern India. The quality of ground water in major part of the study area is generally poor.  In order to understand the shallow groundwater quality, the water samples were collected from 24 dug wells. The primary physical and chemical parameters like potential Hydrogen (pH), Total Dissolved Solids (TDS), Total Hardness (TH), calcium (Ca), magnesium (Mg), sodium (Na), potassium (K), bicarbonate (HCO3), carbonate (CO3), cloride (Cl), sulphate (SO4), nitrate (NO3) and fluoride (F) were analyzed for DWQI. The secondary parameters of irrigation groundwater quality indices such as Sodium Adsorption Ratio (SAR), Sodium Soluble Percentage (SSP), Residual Sodium Carbonate (RSC), Permeability Index (PI), Corrosively Ratio (CR), Magnesium Adsorption Ratio (MAR) and Kellies Ratio (KR) were also derived from the primary parameter for IWQI. The DWQI and IWQI were classified into excellent to unfit condition of groundwater quality based on their Water Quality Index (WQI). The spatial distribution of DWQI (25%) and IWQI (58+26%) indicate that slightly unsustainable to sustainable state of groundwater quality.  Due to this quality deterioration of shallow aquifer, an immediate attention required for sustainable development. Keywords: Groundwater Quality, GIS, Water Quality Indices, Shallow Aquifer, Sustainable Development.